Morfologi dan Distribusi Anaphalis javanica (Astreacea) Di Gunung Galunggung Kabupaten Tasikmalaya - Soendoess, Khadizah; Izmiati, Indri Izni; Hendrawan, Al Maidah; Sofia, Ismi Daru; Gina, Salwa Alya; Putra, Rinaldi Rizal (Universitas Sebelas Maret, 2022)
Mount Galunggung is one of the icons of natural tourism located in Tasikmalaya Regency. The natural beauty that stores various flora and fauna is one of the attractions for people visiting Mount Galunggung. One type of flora found on Mount Galunggung is the edelweiss flower (Anaphalis javanica), which can still be found relatively in the canyon area or the crater rim of Mount Galunggung. Along with the increasing number of tourists visiting Mount Galunggung, A. javanica has been significantly exploited because of the factors taken by tourists. Therefore, this study aimed to determine the morphological characteristics and distribution of edelweiss (A. javanica) in Mount Galunggung, Tasikmalaya Regency. The method used in this research is the descriptive quantitative survey technique. The variables in this study include the morphology and distribution of edelweiss (A. javanica). The study location was in the canyon area of Mount Galunggung, at an altitude of 1,000 – 1,150 meters above sea level. The sampling technique used is purposive sampling with the consideration of locations that are overgrown by edelweiss (A. javanica). The line transect method measuring 2 x 2 m with a transect length of 50 meters was used to obtain distribution data. To obtain morphological data, the key to determining and identifying plant parts was used to van Steenis. The distribution pattern data was processed using the Morisita Index. The results showed that the morphological character of edelweiss in Mount Galunggung refers to the character of Anaphalis javanica, so it is inevitable that the species is Anaphalis javanica. Next, the distribution pattern of A. javanica found in Mount Galunggung is included in the random category, with the Morisita distribution index value of 0.36.